Theories, models, and best practices for decolonizing global health through experiential learning - Hawks, Steven R.; Hawks, Jenna L.; Sullivan, Heather S. (Frontiers in Education, 2023)
The decolonization of global health is increasingly promoted as an essential process for promoting social justice, achieving health equity, and addressing structural violence as a determinant of health. Innovative curricular design for short-term, field-based experiential education activities in global settings represents an important opportunity for bringing about the types of change promoted by the movement to decolonize global health.To identify theories, frameworks, models, and assessment tools for short-term study abroad programs, we conducted a federated search using EBSCOhost on select databases (i.e., Academic Search Ultimate, Medline, CINAHL, and ERIC). A total of 13 articles were identified as relevant to curricular innovations, theories, and designs involving experiential education and learning in global settings that are consistent with the aims of decolonizing global health. The subsequent manuscript review revealed several common themes that inform planning, execution, and evaluation of global experiential education programs.Global education experiences can contribute to decolonization by seeking the interests of host communities. Recommended actions include treating local partners as equals in planning and design, providing compensation to hosts for resources and services rendered, creating opportunities for local practitioners to collaborate, interact, and share knowledge with students, and ensuring the rights of local participants are protected. Additionally, the aims of decolonization are furthered as student participants become aware of and are inspired to dismantle colonial practices. Transformational experiential learning includes engaging students with diverse communities and local knowledge, maximizing participation with local populations and community partners, and engaging in critical thinking and self-reflection culminating in intercultural competence.